2008
DOI: 10.3134/ehtj.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Influenza and respiratory syncytial virus infections in British Hajj pilgrims

Abstract: Viral respiratory infections including influenza and respiratory syncytial virus (RSV) have been reported during the Hajj among international pilgrims. To help establish the burden of these infections at the Hajj, we set up a study to confirm these diagnoses in symptomatic British pilgrims who attended the 2005 Hajj. UK pilgrims with symptoms of upper respiratory tract infection (URTI) were invited to participate; after taking medical history, nasal swabs were collected for point-of-care testing (PoCT) of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 14 publications
2
40
4
Order By: Relevance
“…In these studies, vaccine uptake was higher among individuals considered 'at risk' of developing severe complications from influenza infection, including pilgrims aged over 65 years and those with pre-existing chronic diseases [19,31,45,47]. In two Australian surveys, vaccine uptake was higher among females not considered at risk compared to males not considered at risk in 2011, but not in 2012 [19].…”
Section: Factors Affecting Influenza Vaccine Uptakementioning
confidence: 95%
See 2 more Smart Citations
“…In these studies, vaccine uptake was higher among individuals considered 'at risk' of developing severe complications from influenza infection, including pilgrims aged over 65 years and those with pre-existing chronic diseases [19,31,45,47]. In two Australian surveys, vaccine uptake was higher among females not considered at risk compared to males not considered at risk in 2011, but not in 2012 [19].…”
Section: Factors Affecting Influenza Vaccine Uptakementioning
confidence: 95%
“…The gender distribution was similar in most studies except in eight studies where the majority of respondents were male [11,13,31,33,34,40,43,49]. The included studies are summarised in Appendix 1.…”
Section: Summary Of Included Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…5,6 In summary, of the total 282 swabs tested at the bedside, 9 (3%) were positive for influenza by the QuickVue test. Subsequent testing by RT-PCR on lysis buffer samples, however, showed that 30 patients (11%) had influenza: 22 (73%) influenza A H3, 7 (23%) influenza B, and 1 (3%) influenza A H1.…”
Section: Details Of Ethical Background (Ethics Committee Ref Nomentioning
confidence: 99%
“…5 This study was done as part of enhanced surveillance of influenza and other respiratory viruses among Muslim Hajj pilgrims from the United Kingdom during the Hajj 2005. After obtaining informed consent, 2 nasal swabs were collected from each patient with symptoms of respiratory tract infections who attended or had returned from the Hajj pilgrimage in Mecca, Saudi Arabia.…”
Section: Details Of Ethical Background (Ethics Committee Ref Nomentioning
confidence: 99%